Olfactory Groove Schwannoma—A Case Report and Literature Review - De Cesaro, Marcelo Pedrotti; Araújo, Moisés Augusto; Carli, Fernada de; Manfroi, Gregori; Schwingel, Daniela; Mesquita Filho, Paulo Moacir (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Olfactory groove schwannomas (OGSs) are rare benign tumors of the anterior skull base region. Considering the lack of Schwann cells in the optic and olfactory nerves, their origin remains enigmatic. Despite the precursor cell, total resection of the lesion is curative, as long as the histopathological features of the tumor are compatible with schwannoma. We report the case of a 32-year-old woman, addicted to crack, who was brought to the hospital presenting with cognitive dysfunction after being physically assaulted, whose neuroimaging revealed a large extra-axial mass in the subfrontal sagittal region. The presentation, immunohistochemical markers and histogenesis are discussed in the present study, along with a literature review.
Keywords: olfactory groove schwannoma; olfactory ensheathing cell tumor; anterior skull base; neuroimaging; immunohistochemical; anosmia